2001
DOI: 10.1095/biolreprod64.5.1375
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Morphometry of Bovine Blastocysts Produced In Vivo or In Vitro1

Abstract: The objective of this study was to compare the ultrastructure of bovine blastocysts produced in vivo or in vitro by using morphometric analysis. Blastocysts produced in vivo (multiple ovulations, MO) were obtained from superovulated Holstein cows. For blastocysts produced in vitro, cumulus-oocyte complexes aspirated from ovaries of Holstein cows were matured and fertilized in vitro. At 20 h postinsemination (hpi), zygotes were distributed into one of three culture media: 1) IVPS (in vitro produced with serum):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 47 publications
5
106
1
5
Order By: Relevance
“…Other authors have observed changes in the morphology of preimplantation embryos after culture. Crosier et al (2001) analyzed the ultrastructural morphometry of bovine blastocysts produced in vivo or in vitro using three different culture media and noted that in vitro blastocysts had a smaller nucleocytoplasmic ratio. They associated this finding with reduced quality of in vitro embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have observed changes in the morphology of preimplantation embryos after culture. Crosier et al (2001) analyzed the ultrastructural morphometry of bovine blastocysts produced in vivo or in vitro using three different culture media and noted that in vitro blastocysts had a smaller nucleocytoplasmic ratio. They associated this finding with reduced quality of in vitro embryos.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that embryos developed in serum containing media have a higher proportion of TE cells compared with embryos produced in serum-free media [48]. TE cells are crucial for blastocoele re-expansion and maintenance after cryopreservation, and the higher lipid contents in TE than the ICM [26] could make TE cells particularly damaged during cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…This lower cryotolerance has been associated with the high lipid content present in the cytoplasm of these embryos (Abe et al, 2002;Mucci et al, 2006) and the decrease in the density of mature mitochondria compared to embryos produced in vivo (Crosier et al, 2001;Farin et al, 2004). Additionally, the most abundant lipids in the plasma membranes of cells (phosphatidylcholine and sphingomyelin) also have different profiles (Sudano et al, 2012b).…”
Section: Cryopreservation Of Bovine Embryosmentioning
confidence: 99%